"An act for the better Regulation of the Militia," 5 W.W. Hening, Laws of Va. from First Sess. of Legis. in 1619, Ch. 2 at 17 (1738) - (:unkn) unknown (My University, 1738)
"That every person, so as aforesaid listed, free mulattos, negros and Indians,) and placed or ranked in horse or foot, shall be armed and accoutred in manner following: that is to say, Every horse-man shall be furnished with a serviceable Isorse, a good saddle, with breast-plate, crupper, curb-bridle, carbine or fuzee, and bucket, holsters, a case of pistols, cutting sword or cutlass, double cartouch-box, and six charges of powder,- and constantly appear with the same, at the time and place appointed for muster and exercise; and shall keep at his place of abode, one pound of powder, and four pounds of ball, and bring the same into the field with him, when thereunto required. And every footman shall be furnished with a firelock, musket, or fuzee, well fixed, a bayonet fitted to the same, or a cutting sword or cutlass, a cartouch-box, and three charges of powder"
Keywords: REQUIRED POSSESSION